A new species of Aphanostigme from India - KHAN, M.K. (Indian Phytopathology, 2002)
In Oct. 1986 a new species of Aphanostigme, parasitising Eupatorium in Bihar, India, was identified and is described briefly. The proposed name for the species is A. eupatorii sp.nov.